Reconstituting Water? Climate Change, Water Policy Reform and Community Relations in South Australian Remote Towns. Issue 3 (November 2013) - Wadham, Ben; Boyd, Ross; Willis, Eileen; Pierce, Meryl
Water is a principal medium of exchange within communities facing changing climate patterns and the 'new dry'. For some parts of the globe water has been taken-for-granted, uncontested, yet for others highly variable, scarce and a measure of global and national inequalities. Australia as a large and diverse landmass is emblematic of those varied water contexts, yet as a whole, and after the recent '100-year drought', water has become heavily regulated and marketised, and its material and symbolic meanings transformed. This has led us to ask: "What happens when water becomes marked or recognised as a scarce resource for all, indeed a site of contest and potential human conflict? How do the attempts to control water, through its market currency and environmental value, change the character of communities, the identities and interpersonal relationships that constitute the regional context?" After all, water is about far more than a material resource, it is also a cultural medium that is implicated the most fundamental aspects of life. In this study we explore the ways in which South Australian's living in the arid north of the state, above the Goyder Line, live and identify through the changing relations of water. Those changing relations are the changing availability and governance of water, nested within an ever-present public concern about climate change. We draw upon interviews with settler community members from a 200 square kilometre region across 7 towns or stations. Alongside the growing dry has been the developing commodification of water, having the effect of reducing local autonomy in the management and decision making about water conservation, supply and use. This paper considers the ways that these changes have transformative effects upon the differences and solidarities within local community relations.